Zsub3-connectivity of Ksub{1,3}-free graphs without induced cycle of length at least 5 - Li, Xiangwen (Ars mathematica contemporanea, 2016)
F. Jaeger et al. J. Comb. Theory, Ser. B 56, No. 2, 165--182 (1992) conjectured that every 5-edge-connected graph is ?$Z_3$?-connected. In this paper, we prove that every 4-edge-connected ?$K_{1,3}$?-free graph without any induced cycle of length at least 5 is ?$Z_3$?-connected, which partially generalizes the earlier results of H.-J. Lai Graphs Comb. 16, No. 2, 165--176 (2000) and T. Fukunaga Graphs Comb. 27, No. 5, 647--659 (2011).
Keywords: grafi; teorija grafov